Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Effects of mycobacterium cell wall fraction on embryo development following in vitro embryo production and pregnancy rates following embryo transfer in virgin dairy heifers - W. Brown; M. Oliveira; R. Reis Silva; K. Woodruff; B. Bisha; D. Demetrio; J. Block (Theriogenology, 2024)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

False Ring Formation in Bald Cypress (Taxodium distichum) - Carolyn A. Copenheaver; Jonathan D. Matiuk; Lindsey J. Nolan; Morgan E. Franke; Pamela R. Block; Warren P. Reed; Kathryn R. Kidd; Ghalia Martini (Wetlands, 2017)

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Culture-based methods for detection and identification of Streptococcus agalactiae in pregnant women—what are we missing? - A. Adler; C. Block; D. Engelstein; D. Hochner-Celnikcier; R. Drai-Hassid; A. E. Moses (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Horizontal and vertical movements of juvenile bluefin tuna ( Thunnus orientalis ) in relation to seasons and oceanographic conditions in the eastern Pacific Ocean - TAKASHI KITAGAWA; ANDRE M. BOUSTANY; CHARLES J. FARWELL; THOMAS D. WILLIAMS; MICHAEL R. CASTLETON; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Electronically tagged juvenile Pacific bluefin, Thunnus orientalis , were released off Baja California in the summer of 2002. Time‐series data were analyzed for 18 fish that provided a record of 380 ± 120 days (mean ± SD) of ambient water and peritoneal cavity temperatures at 120 s intervals. Geolocations of tagged fish were estimated based on light‐based longitude and sea surface temperature‐based latitude algorithms. The horizontal and vertical movement patterns of Pacific bluefin were examined in relation to oceanographic conditions and the occurrence of feeding events inferred from thermal fluctuations in the peritoneal cavity. In summer, fish were located primarily in the Southern California Bight and over the continental shelf of Baja California, where juvenile Pacific bluefin use the top of the water column, undertaking occasional, brief forays to depths below the thermocline. In autumn, bluefin migrated north to the waters off the Central California coast when thermal fronts form as the result of weakened equatorward wind stress. An examination of ambient and peritoneal temperatures revealed that bluefin tuna fed during this period along the frontal boundaries. In mid‐winter, the bluefin returned to the Southern California Bight possibly because of strong downwelling and depletion of prey species off the Central California waters. The elevation of the mean peritoneal cavity temperature above the mean ambient water temperature increased as ambient water temperature decreased. The ability of juvenile bluefin tuna to maintain a thermal excess of 10°C occurred at ambient temperatures of 11–14°C when the fish were off the Central California coast. This suggests that the bluefin maintain peritoneal temperature by increasing heat conservation and possibly by increasing internal heat production when in cooler waters. For all of the Pacific bluefin tuna, there was a significant correlation between their mean nighttime depth and the visible disk area of the moon.

A Review of Fine Root Dynamics in Populus Plantations - R. M. A. Block; K. C. J. Van Rees; J. D. Knight (Agroforestry Systems, 2006)

Horizontal movements and depth distribution of large adult yellowfin tuna ( Thunnus albacares ) near the Hawaiian Islands, recorded using ultrasonic telemetry: implications for the physiological ecology of pelagic fishes - R. W. Brill; B. A. Block; C. H. Boggs; K. A. Bigelow; E. V. Freund; D. J. Marcinek (Marine Biology, 1999)

Hydrology, water availability and tundra ecosystem function in a changing climate: the need for a closer integration of ideas? - I. D. Hodkinson; N. R. Webb; J. S. Bale; W. Block (Global Change Biology, 1999)
Hydrologists and ecologists studying tundra ecosystems have worked largely independently, with little cross‐fertilization between disciplines. Their disciplines are, however, inextricably linked by a need to understand the dynamics and significance of the common substance water, in its liquid, solid and gaseous state within tundra environments. The impacts of predicted long‐term changes in climate have particularly important consequences for the functioning of tundra systems and there is a pressing need to initiate studies that integrate hydrological and ecological methodologies and concepts. Our paper attempts to summarize existing information on the role of water within tundra ecosystems, to emphasize the fundamental links between the biotic and the physico/chemical environments and to suggest how a closer integration of ideas might be achieved. Given the breadth of the subject matter the paper is intended to be illustrative rather than comprehensive. The paper examines the physical impacts of water in its various states on the tundra environment, emphasizing in particular the causes of spatial variation in water availability to living organisms. The significance of water is discussed for a range of organism groups, including plants, invertebrates and microorganisms and its pivotal role in ecosystem function and disturbance stressed. The need to develop integrated hydological/ecological models for tundra systems on different spatial scales is emphasized.

Motor learning in the "podokinetic" system and its role in spatial orientation during locomotion - K. D. Weber; W. A. Fletcher; C. R. Gordon; G. Melvill Jones; E. W. Block (Experimental Brain Research, 1998)

Environmental preferences of yellowfin tuna ( Thunnus albacares ) at the northern extent of its range - B. A. Block; J. E. Keen; B. Castillo; H. Dewar; E. V. Freund; D. J. Marcinek; R. W. Brill; C. Farwell (Marine Biology, 1997)